Dynamic Assessment of the Probability of Release Caused by Equipment Deterioration - Maria Francesca Milazzo; Paolo Bragatto; Vincenzo Bartolozzi; Tomaso Vairo; Bruno Fabiano (Chemical Engineering Transactions, 2022)
Deterioration due to the corrosion is the cause of undesired consequences in establishments at major accident hazard as it increases the potential for release of hazardous substances. If the damage mechanisms affecting the equipment are not properly managed, these could give severe impacts in terms of safety as well as business interruption. Risk assessment includes the analysis of scenarios due to the deterioration. Generic probabilities associated with this type of leakage are taken from public database and usually adapted to the industrial context by means of some modification factors. In any case probabilities suffer a major shortcoming that are non-specific, therefore, there is the need to update them based on data collected inside the establishment for each specific equipment. In this work, a dynamic approach for the quantification of the probability of release is presented. Dynamism is here intended as a last-minute update that is following the occurrence of a change inside the establishment. The proposed approach is based on the use of a Fault Trees Analyses (FTA), which integrates additional branches accounting for equipment deterioration; then, the Bayes formula is used to update the generic probability connected to the deterioration by using incident and near-miss reports acquired in real-time. A case-study from a refinery shows the application of the approach and an updated probability of release, which account for the plant-specificity, is obtained.